Pediatric Pleomorphic Adenoma of Parotid Gland: A Case Report - Suryoprabowo, Vincent; Lampus, Harsali F.; Candy, Candy; Saleh, Denny (Universitas Sam Ratulangi, 2025)
Abstract: Pleomorphic adenoma is a type of tumor that affects the parotid glands. It is also called a benign mixed tumor (BMT) because it has both epithelial and myoepithelial cells. This type of tumor is the most frequent parotid gland tumor, making up about 66% of all such tumors in parotid glands. We reported a case of 12-year-old male patient with a lump on his parotid gland, measured 7x3x3cm at Prof. Dr. R. D. Kandou Hospital Manado. CT Scan results of neck region of the patient revealed that there was a mass in the right side colli area and right frontal sinusitis A histopathological examination of the tumor tissue showed that it was encapsulated by connective tissue and composed of proliferating epithelial and myoepithelial tumor cells, some with clear nuclei, arranged in solid and microcystic patterns, and interspersed with fibromyxoid stroma. The patient was diagnosed as parotid gland adenoma, therefore, a parotidectomy was performed on him. He was discharged home and advised to return for a check-up one week later to remove the stitches. At the two-month follow-up visit, he was stable and did not require any additional therapy. In conclusion, a parotidectomy shows good result in the patient with parotid gland adenoma. However, due to the recurrence rate of parotid gland malignancies, several oncologists prefer to observe the patient periodically trough follow up at policlinic. Early detection and right management are required to achieve the best prognosis. Keywords: pleomorphic adenoma; pediatric patient; parotid gland